PCR Tanpa Isolasi DNA dari Sel Epitel Rongga Mulut - Ahmad Saifuddin Noer; Marsia Gustiananda (Institut Teknologi Bandung, 1997)
The polymerase chain reaction (PCR) has become a widely used technique for the amplification of DNA for gene cloning, polymorphisms detection, disease diagnostics, and many others. The starting material for PCR is amount of DNA consist of the sequence interested to be amplified, known as template DNA. Tempate DNA can be obtained in several ways. The preparation of template DNA from muscle tissue by biopsy, blood samples by veni puncture, follicle cells in single hairs, and the cells from urinary tract still have some disadvantages. Some of the methods are invasive, and some of them require DNA isolation steps. In the recent study, we report that preparation of template DNA can be done without isolation steps, and the starting material is mouth epithelial cells obtained from mouth wash fluid. This new method is conducted in the following steps : (i) collecting epithelial cells in mouth wash fluid, (ii) extraction of the cells, (iii) breaking the cells with lysis buffer, (iv) using lysat as a source of template DNA for PCR. Result of this simple procedure showed as 0,4 kb in size band of mitochondrial DNA fragment, that obtained from PCR employing primer M-1 and M-2. PCR without DNA isolation from mouth epithelial cells will be of benefit in the study of population analysis, forensics, and is the potential method for diagnostics.